Stabilization, Safety, and Security of Distributed Systems 15th International Symposium, SSS 2013, Osaka, Japan, November 13-16, 2013. Proceedings - Higashino, Teruo; Katayama, Yoshiaki; Masuzawa, Toshimitsu; Potop-Butucaru, Maria; Yamashita, Masafumi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 15 International Symposium on Stabilization, Safety and Security of Distributed Systems, SSS 2013, held in Osaka, Japan, in November 2013. The 23 regular papers and 12 short papers presented were carefully reviewed and selected from 68 submissions. The Symposium is organized in several tracks, reflecting topics to self-* properties. The tracks are self-stabilization, fault tolerance and dependability; formal methods and distributed systems; ad-hoc, sensors, mobile agents and robot networks and P2P, social, self-organizing, autonomic and opportunistic networks.
Self-stabilization -- Fault tolerance and dependability -- Formal methods and distributed systems -- Ad-hoc, sensors, mobile agents and robot networks -- P2P, social, self-organizing, autonomic and opportunistic networks.
Keywords: Computer science; Computer communication systems; Software engineering; Computer security; Algorithms; Computer logic; Computer Science; Computer Communication Networks; Software Engineering; Information Systems Applications (incl. Internet).; Logics and Meanings of Programs; Algorithm Analysis and Problem Complexity; Systems and Data Security; Electronic books